2006
DOI: 10.1177/0192512106067363
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Distrust of the USA in South Korea

Abstract: The purpose of this article is two-pronged. First, it seeks to identify the factors that seem to lower trust in the USA among South Koreans. These factors weaken the traditionally solid Korea-USA alliance and have led a US expert to call South Korea a "runaway ally." Second, this article empirically tests various explanations of trust using a nationwide survey of South Koreans conducted in 2005. This article employs multiple regression analysis to test the hypothesized relationships. The results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…These data are consistent with studies from various parts of the world showing a significant drop in trust for the United States in reaction to the invasion of Iraq and subsequent events, for example in Mexico (Juarez 2004), South Korea (Kim, Parker, and Choi 2006), China (Johnston and Stockmann 2007), and several Arab states (Chiozza 2007;Lynch 2007). …”
Section: Conditional Effects Of Public Diplomacysupporting
confidence: 86%
“…These data are consistent with studies from various parts of the world showing a significant drop in trust for the United States in reaction to the invasion of Iraq and subsequent events, for example in Mexico (Juarez 2004), South Korea (Kim, Parker, and Choi 2006), China (Johnston and Stockmann 2007), and several Arab states (Chiozza 2007;Lynch 2007). …”
Section: Conditional Effects Of Public Diplomacysupporting
confidence: 86%
“…One is that South Koreans, observing China's rise in economic and political power, increasingly favor closer ties with China over the United States. However, with little empirical support, this view has weakened over time (Chae and Kim 2007; Kim, Parker, and Choi 2006, 437; Kim and Lim 2007, 78–79).…”
Section: Hypotheses Suggested In Rok–us Alliance Literaturementioning
confidence: 99%
“…South Koreans increasingly see the alliance through the prism of its role in inter-Korean reconciliation. Many analysts argue that to continue to maintain the alliance, which was born during the Cold War, a new rationale needs to be found that goes beyond deterrence of North Korean aggression (Kim, Parker, and Choi 2006, 439; Lee 2008, 38). The findings of this study offer just such direction.…”
Section: Attitudes Toward the Rok–us Alliance: Group Comparisonmentioning
confidence: 99%
“…90 Younger South Koreans, like young West Germans before 1989, increasingly regard the US and China with 'moral equivalence' and seem content for the DMZ to become a full-blown border. 91 State Department Asia hands have complained famously for decades that Japan willfully refuses to burden-share with the US in Asia, and the new Hatoyama government speaks openly of a "more equal" relationship with America. Similarly, at least since the Bretton Woods regime, the US Treasury has repeatedly found Japan unwilling to adapt its economic governance to OECD norms.…”
Section: America's Forward Alliance Architecture In Asiamentioning
confidence: 99%